A Study of the Effects of Sexual Immorality Among the Clergy on the Lives of the Christians: A Case of Siaya Town Parish of Ng’iya Deanery, Maseno West Diocese of the Anglican Church of Kenya - Carolyne Anyango Ohanga (Uganda Christian University, 2024)
This study was aimed at investigating the effects of sexual immorality among the clergy on the lives of Christians of Siaya Town Parish of Maseno West Diocese. The study was prompted by observation of some congregants of the mentioned parish leaving the Church to Pentecostal Churches and other Churches after losing confidence in their clergy due to sexual immorality, and also gossip, and eye witnesses’ accounts from congregants concerning sexual misconduct among their clergy. The study sought to examine the cases, the causes, the effects of sexual immorality, and come up with possible remedies to the problem of sexual immorality among the clergy in Siaya Town parish, Maseno West Diocese. A cross-section survey designed was applied in gathering data and total samples of respondents were used. The primary data was collected using structured questionnaire, whereas secondary and tertiary data was collected from authors of different books, journals, and newspapers. Both qualitative and quantitative data were collected. The findings of the study revealed that there have been a number of cases, causes and effects of sexual immorality among clergy of Siaya Town Parish. Practical recommendations to address the problem of sexual immorality among the clergy were also made.
Undergraduate Research